STUDI KOMPARATIF HASIL BELAJAR PKn DAN BAHASA SUNDA MELALUI MODEL TGT PADA SISWA SEKOLAH DASAR - Safitri, Ika; Nabila Al-Adzillah; Mayang Widaningsih; Ina Setiawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was designed to examine and compare learning achievement in Civics (PKn) and Sundanese Language among grade IV students of SDN 4 Awirarangan, Kuningan Regency, Academic Year 2025/2026, following the application of the Team Games Tournament (TGT) cooperative learning model. TGT was chosen because its group-based competitive structure is considered capable of promoting greater student involvement in learning. The study adopted a quantitative approach with a one-group post-test only design involving 21 students as research participants. Data collection was carried out using validated post-test instruments, which were subsequently analyzed through descriptive statistics, the Shapiro-Wilk normality test, and the Wilcoxon Signed-Rank test. Findings revealed a mean score of 60.95 for Civics (38.1% passing rate) and 67.62 for Sundanese Language (71.4% passing rate). Despite this descriptive gap, the Wilcoxon test produced Z = -1.288 with a significance level of 0.198 > 0.05, indicating that H₀ was retained. Accordingly, no statistically significant difference was found between student learning outcomes in the two subjects under the TGT model. These results point to TGT’s potential as a cross-disciplinary instructional approach whose effectiveness is shaped by contextual variables including content difficulty and student readiness. Keywords: learning outcomes, TGT model, Civics, Sundanese Language, elementary school